Snapshot of knowledge and stigma toward mental health disorders and treatment in Spain - Varaona, Andrea; Molina-Ruiz, Rosa M.; Gutiérrez-Rojas, Luis; Perez-Páramo, Maria; Lahera, Guillermo; Donat-Vargas, Carolina; Alvarez-Mon, Miguel Angel (Frontiers in Psychology, 2024)
Background: Mental disorders significantly impact individuals and societies globally. Adressing societal stigma is crucial, as it affects help-seeking behaviors and the effectiveness of treatment for mental disorders. Objective: This study aims to explore the knowledge and perceptions of the Spanish population towards mental disorders and their treatment, assess changes in mental health stigma over time, and examine variations across sociodemographic variables by comparing current results with previous studies. Methods: A panel of three psychiatrists designed a questionnaire to collect public opinions about various aspects of mental illness in Spain, covering topics such as social perception, diagnostic reliability, causes, symptoms, treatment, suicide, and media influence. The survey, conducted from October to December 2022, involved 1002 Spanish individuals aged 18 to 70. Results: Our results indicated an improved general knowledge of mental health, reduced stigma, and greater acceptance of those affected by these disorders, compared to past research. Almost 80% of the participants have accurate knowledge regarding the complex and multifactorial nature of mental illnesses. Around 90% of the participants share the belief that stigma affects those affected by mental disorders. Psychological and pharmacological treatment are considered to be effective and helpful by more than 70% of the sample. More than 60% of the participants highlighted that suicide needs to be addressed appropriately in the media. Conclusions: These findings suggest a significant shift in how Spanish society views mental disorders, marking progress over decades of discrimination. Reducing the stigma associated with mental health can encourage individuals to seek assistance without the fear of judgment or discrimination, thereby increasing the likelihood of early intervention and treatment. Open conversations about mental health within families, communities, and workplaces can create a supportive environment that enhances recovery. However, continued efforts and awareness campaigns targeted to broader audiences remain necessary. Responsible media portrayals of mental health, avoiding stigmatizing language or sensationalism, are also essential.